WRITING LITERACY AS AN EFFORT TO BUILD POSITIVE CHARACTER OF ELEMENTARY SCHOOL STUDENTS - Chandra; Darnis Arief; Annisa Kharisma; M. Habibi, Ari Suriani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The purposes of the study were to analyze the profile of the development of literacy teaching materials in writing prose and produce prototypes of teaching materials for students' prose writing which included the development of positive characters written by elementary school children. Writing habits with the planting of characters familiarize students to be positive following what is usually done. This is based on the character of students currently still concerning. The model of developing prose literacy for elementary students used is the Plomp model with steps: preliminary research, prototyping phase, and assessment phase. Participants in this study, namely experts, elementary students, and elementary school teachers. Data obtained by triangulating data and analyzed by processing quantitative descriptive data. The research findings indicate that the characteristic profile of students tends to be difficult in writing prose essays. The profile of needs analysis shows that elementary students are very fond of fantasy fairy tales, fables, parables, myths, realistic tales, and sage. The prototype of literacy teaching materials writes valid prose according to the needs of students.